Multiple Deformation of Jokotuwo Fault Zone, East Jiwo Hill, Bayat, Klaten, Central Java - Achmad Rodhi; Sutarto Sutarto; Sutanto Sutanto; Sapto Kis Daryono (Techno LPPM, 2022)
Jokotuwo fault zone was first mentioned as the sinistral transpression Jokotuwo fault by Jatmika Setiawan (2002). The trending of fault zone can be traced on four directions. The first direction is ENE –WSW in northern part of Jokotuwo hill to Konang hill. The second direction is E – W in southern part of Jokotuwo hill to southern part of Semangu hill. The third direction is NNW – SSE in central part of Jokotuwo hill to Temas hill, and the fourth direction is NE – SW in central part Jokotuwo hill to Gunung Gajah hill. The fault zone area show evidence for four successive structure episodes. The first generation (D1) is deformation in northern part of Jokotuwo hill to the Rondonom hill. This zones is manifested by a variety of structures for well-developed mylonite foliations. The second generation (D2) is deformation in southern part of Jokotuwo hill to southern part of Semangu hill. This zone is manifested by shearing structure for cataclasite flow. The third generation (D3) is deformation in central part of Jokotuwo hill to Temas hill. This zone is manifested by a variety of structures, which may include drag folds,  fault plane,and fault breccia. The fourth generation (D4) is deformation in central part of Jokotuwo hill to Gunung Gajah hill. This zone  is manifested by a variety of structures, which may include fault plane, and fault breccias. The earliest structures in the Eastern Jiwo hill was generally showed that D1 structures are rotational and non-coaxial in semi-ductile character. The deformation was dextral thrusting involving WNW shortening with a significant component of thrust-parallel slip movement that continued into the Pra-Tertiary Orogeny. The D2 and D3 are rotational and non-coaxial in brittle character. The deformation were sinistral transpressive with a significant component of sinistral-strike slip movement that continued into the Tertiary Orogeny.